2007
DOI: 10.1259/bjr/26858614
|View full text |Cite
|
Sign up to set email alerts
|

Assessing breast tissue density by transillumination breast spectroscopy (TIBS): an intermediate indicator of cancer risk

Abstract: Risk assessment by parenchymal density pattern, a strong physical indicator of future breast cancer risk, is available with the onset of mammographic screening programmes. However, due to the use of ionizing radiation, mammography is not recommended for use in younger women, thereby rendering risk assessment unattainable at an earlier age. Visible and near infrared light was used on 292 women with radiologically normal mammograms to determine whether transillumination breast spectroscopy (TIBS) can identify wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 46 publications
4
49
0
Order By: Relevance
“…In a previous cross-sectional study of 292 women without radiologically suspicious lesions, we showed that TiBS scores (that is, t scores) derived from principal component analysis were highly associated with categorical mammographic density as assessed by a radiologist (23). In this article, we report on the association between TiBS scores and quantitative mammographic features of the breast (percent density, dense area, and nondense area) obtained from analogue films from 104 premenopausal and 121 postmenopausal women from the same cross-sectional study.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…In a previous cross-sectional study of 292 women without radiologically suspicious lesions, we showed that TiBS scores (that is, t scores) derived from principal component analysis were highly associated with categorical mammographic density as assessed by a radiologist (23). In this article, we report on the association between TiBS scores and quantitative mammographic features of the breast (percent density, dense area, and nondense area) obtained from analogue films from 104 premenopausal and 121 postmenopausal women from the same cross-sectional study.…”
Section: Introductionmentioning
confidence: 87%
“…The instrumentation used to gather transillumination spectra was described previously in detail and is depicted in Fig. 1 (20)(21)(22)(23). A 50 W halogen lamp served as broadband light source; 200 mW light of wavelength 550 to <1,300 E was coupled into a 5-mm-diameter liquid light guide (Fibre Guide) placed in contact with the skin on top of the breast with minimal compression.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus far, a few groups applied statistical analysis techniques to multiparameter optical measurements, including applications to arthritic joints, 16 high-risk 17 or high mammographic density 18,19 breast tissue, and to various "endo-scopic" measurements or excised tissues. 20 The data sets employed thus far, however, have limited spatial information and orders of magnitude fewer measurements per subject than, for example, the breast tomograms utilized in the analysis to be presented herein.…”
Section: Ib Limitations Of Current Diffuse Optics Analysismentioning
confidence: 99%